Environmental and Legal Framework for Regulating Consumer and Industrial Waste Management - BEKEZHANOV, Dauren; OMIRALI, Alima; AITIMOV, Bolat; NURMUKHANKYZY, Daniya; ZHUMAGULOV, Timur (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020DO - 10.14505//jemt.v11.1(41).21, 2020)
The purpose of the research is to study and substantiate ways to solve problems in the field of environmental legislation of the Republic of Kazakhstan on the treatment of consumer and industrial waste by solving them. The article is devoted to the study of the current state and prospects of development of the environmental legislation of the Republic of Kazakhstan on the treatment of consumer and industrial waste. However, the issue under consideration cannot be limited to an analysis of environmental law. The problem of handling consumer and industrial waste is regulated by the rules of state regulation in the field of handling consumer and industrial waste and the use of international and other branches of law. Research topics are broad in nature, which determines the complexity of the study.